Supported catalysts based on layered double hydroxides for catalytic oxidation and hydrogenation: general functionality and promising application prospects - Feng, Junting; He, Yufei; Liu, Yanan; Du, Yiyun; Li, Dianqing (Chemical Society reviews, 2015)
Oxidation and hydrogenation catalysis plays a crucial role in the current chemical industry for the production of key chemicals and intermediates. Because of their easy separation and recyclability, supported catalysts are widely used in these two processes. Layered double hydroxides (LDHs) with the advantages of unique structure, composition diversity, high stability, ease of preparation and low cost have shown great potential in the design and synthesis of novel supported catalysts. This review summarizes the recent progress in supported catalysts by using LDHs as supports/precursors for catalytic oxidation and hydrogenation. Particularly, partial hydrogenation of acetylene, hydrogenation of dimethyl terephthalate, methanation, epoxidation of olefins, elimination of NO x and SO x emissions, and selective oxidation of biomass have been chosen as representative reactions in the petrochemical, fine chemicals, environmental protection and clean energy fields to highlight the potential application and the general functionality of LDH-based catalysts in catalytic oxidation and hydrogenation. Finally, we concisely discuss some of the scientific challenges and opportunities of supported catalysts based on LDH materials. This review focuses on the recent progress in supported catalysts based on LDH for use in catalytic hydrogenation and oxidation.